Penggunaan Media Film Dalam Proses Pembelajaran Sejarah Kebudayaan Islam di MA-Muhammadiyah 1 Plus Malang - Suherman Suherman; Sunarto Sunarto; Aprin Alpajar (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Use of Film Media in the Learning Process of Islamic Cultural History at MA Muhammadiyah 1 Plus MalangThe focus of this research is on how to implement film media in the learning process of Islamic Cultural History and the learning outcomes of Islamic Cultural History using film media. This research is classified as qualitative research with a type of case study. While the study of data on the author's research conducted observations, interviews, and documentation. The results of the research on the use of film media in the learning process of the history of Islamic culture show that: (1) The application of film media in the lesson of Islamic cultural history, there are several steps taken by the teacher before the learning process, namely, planning, class preparation, presentation, follow-up activities. (2) The results of using film media in the lessons of Islamic cultural history show good results. Film media can increase learning activeness and enthusiasm, film media criteria provide understanding in understanding subject matter, students are able to answer questions and answer questions, film media can increase learning values and achieve minimal completeness.Abstract: Penggunaan Media Film Dalam Proses Pembelajaran Sejarah Kebudayaan Islam di MA Muhammadiyah 1 Plus MalangPenelitian ini fokus kepada implementasi media film dalam proses pembelajaran Sejarh Kebudyaan Islam dan hasil pembelajaran Sejarah Kebudayan Islam menggunakan media film .Penelitian ini tergolong dalam penelitian kualitatif dengan dengan jenis studi kasus. Sedangkan pengumpulan data terhadap pelaksanaan penelitian penulis melakukan observasi, wawancara, serta dokumentasi. Hasil penelitian penggunaan media film dalam proses pembelajaran sejarah Kebudayaan Islam menunjukkan bahwa: (1) Implemplementasi media film pada pelajaran sejarah kebudayaan Islam terdapat beberapa langkah yang dilakukan oleh guru sebelum proses pembelajaran yaitu, perencanaan, persiapan kelas, penyajian, aktivitas lanjutan. (2) Hasil penggunaan media film pada pelajaran sejrah kebudayan Islam menunjukkan hasil yang baik. Media film mampu meningkatkan keaktifan dan semangat belajar, media film memberikan kemudahan dalam memahami materi pelajaran, peserta didik mampu mengerjakan soal dan menjawab pertanyaan, media film mampu meningkatkan nilai belajar dan mencapai Kriteria Ketuntasan Minimal.